Democracies in Action: A Changing Learning Community Landscape (LEARNing Landscapes, 2011)
Learning alongside others to effect transformation of community and self is a process of inquiry that guides theory and practice. My purpose as an author is to portray a balanced, realistic portrait of the promises and pitfalls of engaging in professional learning communities (PLCs). Herein I present the results of a democratic project that united 42 scholars and practitioners who made discoveries as collaborators within evolving communities of practice geared toward desirable change. I also draw upon the relevant literature to describe this trend and identify possibilities for renewal, reflection, and inquiry that arise out of PLCs.
Keywords: inquiry; self; transformation; professional learning; community; change